Genus Eteoryctis Kumata & Kuroko, 1988 (Lepidoptera: Gracillariidae) in Korea with description of a new species - Kim, Da-Som; Byun, Bong-Kyu (Zootaxa, 2022)
In this study, three species of the genus Eteoryctis Kumata & Kuroko, 1988 are recognized from Korea. Among them, E. minimus sp. nov. is described as new to science. Also, one species, E. picrasmae Kumata & Kuroko, 1988 is reported for the first time from Korea. Adults and genitalia of all species are described and illustrated. Also, a key to the species of Eteoryctis in Korea is presented.